Pedro Casaldáliga: The prophecy of a prophet shepherd - Franguelli, Bruno (Razón y fe, 2022)
On August 8, 2020, the Catalan missionary in Brazil, Pedro Casaldáliga, passed away at the age of 92. The bishop of the forgotten consecrated his life totally to prophetic pastoral work and the tireless defense of the oppressed. He left a legacy of words, gestures, and a radical commitment to the life of the poor. Far from any privilege offered by his ecclesiastical position, he embraced wholeheartedly what the Spirit suggested to the Latin American Church through the Medellin document: the preferential option for the poor.